Improved method for detecting a low-altitude, low-speed aerial object in the presence of ground clutter using a synchronous multi-radar system - Khudov, Hennadii; Lukianchykov, Andrii; Tiutiunnyk, Vladyslav; Komarov, Volodymyr; Salnyk, Oleh; Kotov, Denys; Maliuha, Volodymyr; Prystinskyi, Roman; Vlasiuk, Valerii; Popov, Serhii (Eastern-European Journal of Enterprise Technologies, 2026)
This study considers the process of detecting a low-altitude, low-speed air object in the presence of ground clutter. The principal hypothesis assumes that improving the method could make it possible to increase the signal/noise ratio. A method has been improved for detecting a low-altitude, low-speed air object in the presence of ground clutter using a synchronous multi-radar system, which, in contrast to known ones, allows for the following: – a synchronous survey of the airspace in azimuth and range by two radars by emitting mutually orthogonal probing signals; – forming signals reflected from the air object at the output of the radar receivers; – incoherent, joint signal processing in a synchronous multi-radar system from two survey radars; – coordinated filtering of received signals; – formation of Doppler channels; – equalization by delay time and Doppler frequency; – formation of an additive processing channel where incoherent summation of signals is carried out and formation of air object detection marks in the additive channel; – formation of a multiplicative processing channel where multiplication of signals is carried out and formation of air object detection marks of the multiplicative channel; – combination of air object detection marks of the additive and multiplicative channels and formation of final detection marks. An experimental study was conducted on the detection of a low-altitude, low-speed air object. The use of a synchronous multiradar system made it possible to increase the signal/noise ratio by 4 times. Additional multiplicative signal processing provides an increase in the signal/noise ratio and improves the discrimination of the signal from the air object in the presence of ground clutter